STUDIES ON SOLID DISPERSIONS OF LEFLUNOMIDE - PR, MAHAPARALE; VP, THORAT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Leflunomide is Non steroidal Anti-Inflammatory drug, which is poorly water soluble. In present study attempt has been made to prepare and characterize solid dispersions of leflunomide to increase solubility of drug. Method: Â In Preparation of solid dispersion of leflunomide different polymer like PEG 4000, PEG 6000, Poloxamer 188 and Poloxamer 407 were used. Â Effects of several variables such as type of carrier used, drug: carrier ratios, method of preparation were studied. The evaluation of solid dispersions was done by solubility study, dissolution study and X-ray diffractometry. Â Result: Improvement in dissolution of drug was observed in all solid dispersions as compared to pure drug alone. Solid dispersions prepared using Poloxamer 188 showed fastest in vitro drug release. Solid dispersions prepared using solvent evaporation method showed relatively faster drug release than melt evaporation method. XRD patterns indicated reduced crystallinity of drug particles, which suggests mechanism of enhanced solubility and dissolution of drug in solid dispersion systems. Conclusion: Â A significant result obtained with the study indicated that solid dispersion by solvent evaporation can successfully be further explored and employed to improve solubility and dissolution characteristics of poorly soluble drugs. Keywords: Leflunomide, Solid dispersion, Carrier